2004
DOI: 10.1073/pnas.0401885101
|View full text |Cite
|
Sign up to set email alerts
|

Dynamers: Polyacylhydrazone reversible covalent polymers, component exchange, and constitutional diversity

Abstract: Component exchange in reversible polymers allows the generation of dynamic constitutional diversity. The polycondensation of dihydrazides with dialdehydes generates polyacylhydrazones, to which the acylhydrazone functionality formed confers both hydrogen-bonding and reversibility features through the amide and imine groups, respectively. Polyacylhydrazones are thus dynamic polyamides. They are able to reversibly exchange either one or both of their repeating monomer units in the presence of different monomers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
207
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(209 citation statements)
references
References 39 publications
2
207
0
Order By: Relevance
“…Within this context, we previously showed that dynamic covalent polymers, [15] or dynamers, [20][21][22][23] generated from reversibly interacting monomers, offer the possibility to address these issues. [24,25] In dynamers, the components are reversibly connected, and they self-assemble in such a fashion that their overall morphology overrides defects during the forAbstract: Obtaining high permeability whilst keeping a reasonable selectivity is the most important challenge in the development of membrane systems for gas separation.…”
mentioning
confidence: 99%
“…Within this context, we previously showed that dynamic covalent polymers, [15] or dynamers, [20][21][22][23] generated from reversibly interacting monomers, offer the possibility to address these issues. [24,25] In dynamers, the components are reversibly connected, and they self-assemble in such a fashion that their overall morphology overrides defects during the forAbstract: Obtaining high permeability whilst keeping a reasonable selectivity is the most important challenge in the development of membrane systems for gas separation.…”
mentioning
confidence: 99%
“…Numerous hydrazine derivatives are commercially available or can easily be prepared in a few reaction steps (see, e.g., [16]). Particularly interesting in the context of the present studies are acylhydrazines (¼ hydrazides; R'COÀNHÀNH 2 ), as these compounds incorporate a peptide bond together with the imine-forming hydrazine functionality [17]. For our studies, we used alkyl-or arylhydrazines 1a and 2a, sulfonylhydrazine (¼ sulfonic acid hydrazide) 3a, as well as a series of different hydrazides such as semicarbazide (¼ hydrazinecarboxamide) 4a, hydrazinecarboxylate 5a, furoyl-and arylhydrazides (¼ furan-and arenecarboxylic acid hydrazides) 6a -8a, alkylhydrazides (¼ alkanoic acid hydrazides) 9a and 10a, and the Girard T (11a) or P (12a) reagents [18] (Fig.…”
mentioning
confidence: 99%
“…Indeed, recent work has uncovered the presence of a binding pocket in the middle of the gorge of the enzyme, a fact in line with the strong activity of the bis-pyridinium inhibitor containing a disubstituted para-phenylene spacer [74]. The field of DCC has been the subject of great interest and activity since the formulation of the concept, as shown by the development of new approaches, e. g. dynamic combinatorial X-ray crystallography [60] or pseudo-dynamic chemistry [49], application of new reversible reactions for DCL generation [44,45] and application to materials science, as for instance in the case of dynamic polymers-dynamers [75][76][77] and the formation of G-quartet-based hydrogels [78].…”
Section: Discussionmentioning
confidence: 99%